Structure, Crystallization and Thermal Behavior of Fluorinated ethylene propylene (FEP) based Plastics Composites - Chen Jian-bing; Li Zhun-zhun; Xu Nan (Functional Materials, 2018)
The FEP based binary and ternary plastics composites were prepared by melt blending. The microstructure, crystallization behavior and thermal degradation behavior of FEP/PEEK, FEP/PEI and FEP/PEEK/PEI composites were investigated by FT-IR, SEM, DSC, XRD and TGA. The FT-IR, SEM and DSC results shows that the FEP/PEEK, FEP/PEI and FEP/PEEK/PEI composites were presented thermodynamics incompatible. The degree of crystallinity of FEP was decreased as PEEK or with PEI simultaneously were added to FEP matrix, while the degree of crystallinity of FEP increases first then decreases as PEI was added to FEP matrix. The TGA results shows that the thermal stability of FEP/PEEK composites enhance with PEEK content increases when the PEEK content is under 25%, then decreased when the PEEK content is over 25%, the thermal stability of FEP/PEI and FEP/PEEK/PEI composites decreased with PEI or PEEK added to the FEP matrix.